Obamacare on Twitter - Rico Méndez, Gina (Teorija in praksa, 2018)
As Internet-based communications have expanded, online debating has become a significant form of political participation. This work examines online discussions around health care in the United States by analysing tweets about Obamacare and then assessing the degrees of polarisation in social media. The results indicate that highly influential entities in social media have an important capacity to polarise the public. Another relevant finding is that ideology is a powerful mechanism to frame online discussions by relegating policy arguments in online debates. Finally, this work shows that social media can easily promote negative sentiments towards "the other", confirming group homogeneity in online communities.
Keywords: Družbeni mediji; Health care reform; Polarizacija; Polarization; Political participation; Politična participacija; Reforma zdravstvenega varstva; Social media